2004
DOI: 10.1111/j.1365-2265.2004.01989.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of different treatment options for non‐islet cell tumour hypoglycaemia

Abstract: Within the limits of the cases studied, and the time-scales involved, moderate- to high-dose glucocorticoid therapy had immediate beneficial influence on symptomatic hypoglycaemia and, if tolerated in the long term, was effective in correcting the underlying biochemical dysfunction, unlike other therapeutic regimens. This effectiveness was only achieved when the dose exceeded a threshold level specific to the patient. In addition, reduction of the dose or withdrawal of the drug caused a return of the abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 12 publications
(17 reference statements)
1
90
0
3
Order By: Relevance
“…ternary complex formation (3,12). Successful treatment of hypoglycemia has been described in several case reports and series, with response rates appearing to be dose dependent (3,(6)(7)(8)(9). Despite these positive responses, there are scattered reports of refractory hypoglycemia on high doses of glucocorticoids, as in our patient.…”
Section: Discussionmentioning
confidence: 65%
“…ternary complex formation (3,12). Successful treatment of hypoglycemia has been described in several case reports and series, with response rates appearing to be dose dependent (3,(6)(7)(8)(9). Despite these positive responses, there are scattered reports of refractory hypoglycemia on high doses of glucocorticoids, as in our patient.…”
Section: Discussionmentioning
confidence: 65%
“…Thereafter, the dose of prednisolone was tapered to 15 mg/day, but his blood glucose levels were stable and hypoglycemia no longer occurred. (2,9,10 (4,5,8,11,12) (4,5,13). Surgical resection led to normalization of the plasma glucose levels in all five cases.…”
Section: F I G U R E 4 Cl I N I C a L C O U R S E Hy P O G L Y C mentioning
confidence: 78%
“…Interestingly, five of six cases treated with glucocorticoid therapy no longer suffered from hypoglycemic attacks in spite of receiving no anti-tumor treatment (16,17). On the other hand, three of four cases treated with dextrose infusion alone had repeated hypoglycemic episodes (18) (6,13,19). In addition, glucocorticoid may inhibit the tumor growth, because IGF-II is one of the autocrine growth factors for the tumor (20).…”
Section: F I G U R E 4 Cl I N I C a L C O U R S E Hy P O G L Y C mentioning
confidence: 99%
“…In a previous report, Teale et al reported that glucocorticoid therapy suppressed abnormal secretion of big-IGF-II in a case of NICTH (24). To understand the effect of glucocorticoid treatment, we must clarify the molecular changes in NICTH.…”
Section: Discussionmentioning
confidence: 99%